2015
DOI: 10.1021/acs.organomet.5b00710
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Ether Cleavage by Group 9 and 10 Transition Metals: Stoichiometric Studies of Selectivity and Mechanism

Abstract: (38a). S16II. Crystallographic Data S17 Table S1. Crystal and refinement data for 5a, 8a, 19a, 26a. S17 Table S2. Crystal and refinement data for 28a, 32b, 34a, 38a. S17

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 102 publications
0
22
0
Order By: Relevance
“…39 Pt spectrum which showed a triplet at 5285 (J(PtP) 3804 Hz) and 1 H-195 Pt HMQC spectra. The tetrafluoropyridinolate anion exhibited two resonances in the 19 F NMR spectra and three resonances with 19 F coupling in the 13 C NMR spectra (see Experimental section). It is significant that the complex is only slightly soluble in benzene unlike the neutral Pt complexes described in ref 21.…”
Section: Experimental and Computational Reactivity Toward 2356tetrmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Pt spectrum which showed a triplet at 5285 (J(PtP) 3804 Hz) and 1 H-195 Pt HMQC spectra. The tetrafluoropyridinolate anion exhibited two resonances in the 19 F NMR spectra and three resonances with 19 F coupling in the 13 C NMR spectra (see Experimental section). It is significant that the complex is only slightly soluble in benzene unlike the neutral Pt complexes described in ref 21.…”
Section: Experimental and Computational Reactivity Toward 2356tetrmentioning
confidence: 99%
“…12 Intramolecular CO alkyl cleavage at Pd(0) and Pt(0) has also been reported briefly. 13 Additionally, C(sp 3 ) O bond activation reactions have been achieved using esters at Ir, Fe, and Pt complexes. 11,14,15 Closely related to C O activation is the microscopic reverse, C O formation, reported by several authors.…”
Section: Introductionmentioning
confidence: 99%
“…Zuschriften the rhodium-catalyzed conditions in the absence of an arene substrate,n aphthalene (5)w as formed in 56 %y ield (Scheme 5a). This observation indicates that Rh I (L6) 2 can activate the C À Ob ond of 2a,p resumably through oxidative addition, [9] and the resulting arylrhodium(III) species undergoes protonation to form 5.L abeling studies revealed that Rh I -(L6) 2 can also activate aC ÀHb ond (Scheme 5b). When deuterated arene 1a-d 7 was reacted with 2a in the presence of aR h I (L6) 2 catalyst for 1h(62 %c onversion), the deuterium content of the recovered 1a was significantly reduced.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…To realize the cross-coupling of unactivated CÀHb onds with inert phenol derivatives,the catalyst needs to efficiently mediate the activation of both CÀHa nd CÀOb onds.B ased on its remarkable activity in C À Hactivation, [8] we decided to use ar hodium catalyst, even though rhodium complexes are rarely used for C À Ob ond activation processes. [9] Reported rhodium complexes that can activate the C(aryl)ÀOb ond require the use of ap incer-type ligand [9a,b] or boron-based reagents, [9c-e] both of which cannot be directly applied to our target CÀH/CÀOc ross-coupling reactions.W ec hose ortho arylation of 1a [10] with aryl carbamate 2a as our model reaction for catalyst development. It should be noted that the oxazoline substrates are readily accessible from the corresponding carboxylic acids through condensation with 2aminopropan-1-ol.…”
mentioning
confidence: 99%
“…This observation indicates that Rh I (L6) 2 can activate the C À Ob ond of 2a,p resumably through oxidative addition, [9] and the resulting arylrhodium(III) species undergoes protonation to form 5.L abeling studies revealed that Rh I -(L6) 2 can also activate aC ÀHb ond (Scheme 5b). When aryl carbamate 2a was subjected to the rhodium-catalyzed conditions in the absence of an arene substrate,n aphthalene (5)w as formed in 56 %y ield (Scheme 5a).…”
mentioning
confidence: 99%